Political Communication of DKI Jakarta DPRD Members in Regional Regulation Decision-Making: A Case Study of the Debate on the Reclamation Draft Regulation (Oratio Directa, 2018)
Political communication is part of the activities of a political system through which public aspirations and interests are articulated into policy. This study examines the political communication of members of the Jakarta Regional House of Representatives (DPRD DKI Jakarta) in deliberating decisions on the Reclamation Regional Regulation. A qualitative case-study approach was used, with primary data from interviews and secondary data from document and literature review. The findings show that DPRD DKI Jakarta performs oversight, budgeting, and legislative functions through commissions, the Regional Legislative Body, and the Ethics Council. These bodies connect the legislature with the executive. The formulation of the Reclamation Regional Regulation therefore requires political communication between DPRD DKI Jakarta and the provincial government to coordinate legislative initiatives and prevent duplicate draft regulations.
Keywords: Political communication; DPRD DKI Jakarta; Legislative function; Reclamation regulation; Decisionmaking